Can Community Social Cohesion Prevent Posttraumatic Stress Disorder in the Aftermath of a Disaster? A Natural Experiment From the 2011 Tohoku Earthquake and Tsunami - Hikichi, Hiroyuki (Am J Epidemiol, 2016)
In the aftermath of a disaster, the risk of posttraumatic stress disorder (PTSD) is high. We sought to examine whether the predisaster level of community social cohesion was associated with a lower risk of PTSD after the earthquake and tsunami in Tohoku, Japan, on March 11, 2011. The baseline for our natural experiment was established in a survey of older community-dwelling adults who lived 80 kilometers west of the epicenter 7 months before the earthquake and tsunami. A follow-up survey was conducted approximately 2.5 years after the disaster. We used a spatial Durbin model to examine the association of community-level social cohesion with the individual risk of PTSD. Among our analytic sample (n = 3,567), 11.4% of respondents reported severe PTSD symptoms. In the spatial Durbin model, individual- and community-level social cohesion before the disaster were significantly associated with lower risks of PTSD symptoms (odds ratio = 0.87, 95% confidence interval: 0.77, 0.98 and odds ratio = 0.75, 95% confidence interval: 0.63, 0.90, respectively), even after adjustment for depression symptoms at baseline and experiences during the disaster (including loss of loved ones, housing damage, and interruption of access to health care). Community-level social cohesion strengthens the resilience of community residents in the aftermath of a disaster.